Phenology-dependent cold exposure and thermal performance of Ostrinia nubilalis ecotypes. - Wadsworth, Crista B.; Okada, Yuta.; Dopman, Erik B. (Tufts University. Tisch Library., 2020)
Keywords: Thermal tolerance, Seasonal timing, Phenology, Cold-hardiness, Climate adaptation, Diapause, Adaptation by time.; Springer Open.